A Case of Fever of Unknown Origin “The Clinical Case Series of Cerrahpaşa” - Yıldız Kaya, Sibel; Fansa, Sezen; Asa, Sertaç; Özdede, Ayşe; Seyahi, Emire; Tabak, Fehmi (Cerrahpaşa Medical Journal, 2025)
Cite this article as: Kaya SY, Fansa S, Asa S, Özdede A, Seyahi E, Tabak F. A case of fever of unknown origin: “the clinical case series of Cerrahpaşa”. Cerrahpaşa Med J. 2025; 49, 0026, doi: 10.5152/cjm.2025.24026.